Microglia maintain the normal structure and function of the hippocampal astrocyte network - Du, Yixing; Brennan, Faith H.; Popovich, Phillip G.; Zhou, Min (Glia, 2022)
Microglial control of activity‐dependent plasticity and synaptic remodeling in neuronal networks has been the subject of intense research in the past several years. Although microglia–neuron interactions have been extensively studied, less is known about how microglia influence astrocyte‐dependent control over neuronal structure and function. Here, we explored a role for microglia in regulating the structure and function of the astrocyte syncytium in mouse hippocampus. After depleting microglia using a CSF1R antagonist (PLX5622, Plexxikon), we observed severe disruption of astrocyte syncytial isopotentiality and dye coupling. A decrease in astrocyte‐specific gap junction connexin (Cx) 30 and 43 expression, at least partially accounts for these microglia‐dependent changes in astrocytes. Because neuronal function requires intact astrocyte coupling, we also evaluated the effects of microglia depletion on synaptic transmission in the hippocampus. Without microglia, the strength of synaptic transmission was reduced at baseline and after long‐term potentiation (LTP). Conversely, priming microglia with systemic injections of lipopolysaccharide enhanced CA3‐CA1 synaptic transmission. This microglia‐induced scaling of synaptic transmission was associated with increased expression of post‐synaptic scaffold proteins (Homer1) in CA1. However, astrocyte network function was not affected by microglia priming, indicating that microglia‐dependent effects on astrocytes and neurons vary across functional states. Through manipulation of microglia in the brain, our results reveal the importance of microglia in homeostatic regulation of the astrocyte syncytium and scaling of synaptic transmission. These novel mechanisms uncover a new direction for future studies interrogating microglia function in various physiological and pathological contexts. Main Points Microglia maintain expression of astrocyte connexins, gap junctional coupling, and astrocyte syncytial isopotentiality in mouse hippocampus. Microglia enable bidirectional scaling of synaptic transmission, partly by modulating postsynaptic Homer1.